The Gendered Face of Islamic Terrorism in Nigeria (Hekima Review, 2014)
Women and girls are disproportionately affected in the Boko Haram crisis in northern Nigeria that has claimed more than five thousand lives since its inception in 2009. Women have been used as war tools to shame, humiliate and take revenge on the government. They are raped, sexually assaulted and violated in different ways. This reached a climax with the abduction of 276 secondary school girls by the Boko Haram militant group in April, 2014. Recently, the militant group has evolved a tactic of using women and girls as suicide bombers. Despite resistance from women and other groups it has continued. For this to stop, brave men and women will have to stand up.